Learning Design – creative design to visualise learning activities. (1st September 2016) - Toetenel, Lisette; Rienties, Bart
Abstract: The focus on quality improvements by institutions for better online and blended teaching can be delivered in different ways. This article reports on the implementation of this process and the approaches taken first, in terms of the design of new learning materials, and second, when reviewing the existing curriculum. The study aims to ascertain whether the combination of a collaborative, networked approach at the initial design stage, augmented with visualisations, has changed the way educators design their courses at The Open University, UK. Analysis of 148 learning designs shows both before and after the introduction of Learning Design, which of the pedagogic decisions that educators made substantially changed. Courses that were designed after the introduction of Learning Design were more focused on the development of a range of skills and included fewer assimilative activities (reading, watching videos and listening to audio). Our findings suggest that by visualising the design upfront, educators focused less on traditional teaching patterns, such as the 'teach, practice, apply' model. Remarkably, just by visualising initial decisions and working in collaborative workshops, educators created more student-centred and creative designs aimed to develop a range of skills which support students in both their studies and the workplace. Further studies are needed to establish whether these pedagogic decisions have an impact on student outcomes and whether these findings can be replicated in different institutions.